Innovation and economic growth in middle-income countries: The moderating role of remittances - Islam, Md Zahidul; Masum, Md; Islam, Md Farijul; Nabi, Md Nurun; Rahman, Mohammad Sayedur (Asian Journal of Economic Modelling, 2025)
The prime objective of this paper is to examine the direct and moderating role of remittances in the innovation-growth nexus in MICs. Middle-income countries (MICs) can drive global economic growth by utilizing 75% of the population through technological development and boosting GDP by over one-third of the total. However, using human resources effectively and maintaining technical advancement standards in response to rapid economic changes remain a significant challenge. The study utilizes the "2nd generation unit root test and the panel corrected standard errors (PCSE) and the feasible generalized least squares (FGLS)" approaches. The FGLS and "Dumitrescu-Hurlin (D-H)" causality tests are applied to confirm the robustness of the PCSE approach. The study highlights the distinct and interconnected effects of remittances and innovation on economic growth in MICs, emphasizing their mutually reinforcing role in sustained growth. The interactive span demonstrates that remittances functioned as a substitute in the innovation-growth association. Finally, the study reveals a bidirectional causal affiliation between remittances and economic growth and a unidirectional causal connection between economic growth and innovation. MICs should enhance remittance transfer systems, invest in innovation, enhance skills, utilize public-private partnerships for efficient allocation, and balance entrepreneurship with macroeconomic stability.